2000
DOI: 10.1093/emboj/19.1.103
|View full text |Cite
|
Sign up to set email alerts
|

A conformational switch controlling HIV-1 morphogenesis

Abstract: Assembly of infectious human immunodeficiency virus type 1 (HIV-1) proceeds in two steps. Initially, an immature virus with a spherical capsid shell consisting of uncleaved Gag polyproteins is formed. Extracellular proteolytic maturation causes rearrangement of the inner virion structure, leading to the conical capsid of the infectious virus. Using an in vitro assembly system, we show that the same HIV-1 Gag-derived protein can form spherical particles, virtually indistinguishable from immature HIV-1 capsids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
269
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(290 citation statements)
references
References 45 publications
19
269
1
Order By: Relevance
“…In support of this idea, removal of SP1 can cause recombinant HIV-1 Gag proteins to switch from immaturelike spherical assemblies to mature-like cylinders in vitro [13]. As discussed above, the CA-SP1 region appears to stabilize the immature Gag hexamer, and proteolysis at the CA-SP1 junction therefore presumably destabilizes the Gag lattice.…”
Section: Retroviral Maturationmentioning
confidence: 79%
See 1 more Smart Citation
“…In support of this idea, removal of SP1 can cause recombinant HIV-1 Gag proteins to switch from immaturelike spherical assemblies to mature-like cylinders in vitro [13]. As discussed above, the CA-SP1 region appears to stabilize the immature Gag hexamer, and proteolysis at the CA-SP1 junction therefore presumably destabilizes the Gag lattice.…”
Section: Retroviral Maturationmentioning
confidence: 79%
“…To a first approximation, all of the information necessary for retroviral particle assembly resides in the Gag polypeptide. For example, Gag alone can form extracellular virus-like particles in the absence of other viral proteins [11] and Gag molecules can spontaneously assemble into spherical, immature viruslike particles in vitro [12][13][14]. Nevertheless, although Gag itself encodes the necessary tertiary and quaternary interactions, it must be emphasized that assembly requires nonspecific RNA interactions both in vivo and in vitro, and is assisted by host factors in vivo, including trafficking factors, assembly chaperones, and the ESCRT budding pathway, as reviewed elsewhere [15][16][17][18].…”
Section: Gag As An Assembly Machinementioning
confidence: 99%
“…1A) (19,20,24), which have a mature-like arrangement of CA. Prior studies had indicated that certain HIV-1 Gag-derived proteins can assemble tubular or spherical particles depending on the conditions (22) and that certain mutations in the CA-SP1 region converted the assembly from spherical to tubular or aberrant sheet-like structures (12,25). Furthermore, mutations in the region targeted by the capsid assembly inhibitor CAI do not alter assembly of immature particles in vitro or in tissue culture, whereas they completely disrupt assembly of the mature-like lattice (26).…”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 Gag derivatives that assemble tubular arrays adopt a mature-like arrangement of CA (19,20), and have indeed been important tools in determining the structure of the mature CA core (9,21). In contrast, HIV-1 Gag derivatives known to assemble into immature-like arrays form approximately spherical structures (22,23) that are unsuitable for application of high-resolution helical reconstruction methods.…”
mentioning
confidence: 99%
“…Taking into account the participation of SP1 in each of the multimerization process (26,30,61), viral maturation (24,25), and recognition of the HIV-1 ⌿ site by NC (31,32), we decided to study relevant RNA-protein interactions in vitro using a minimal Pr55 Gag (mGag) protein. This recombinant protein includes amino acids 2-7 of MA (the myristyl anchor), the CTD of CA, SP1, and NC (28).…”
mentioning
confidence: 99%